Changes in arterial blood pressure caused by long-term administration of grape seed proanthocyanidins in rats with established hypertension. Issue 10 (18th September 2020) - Mas-Capdevila, Anna; Iglesias-Carres, Lisard; Arola-Arnal, Anna; Suárez, Manuel; Bravo, Francisca I.; Muguerza, Begoña
Abstract : The development of hypertension (HTN) in cafeteria (CAF) diet-fed rats was demonstrated to be attenuated after grape seed proanthocyanidin extract (GSPE) administration. Abstract : The development of hypertension (HTN) in cafeteria (CAF) diet-fed rats was demonstrated to be attenuated after grape seed proanthocyanidin extract (GSPE) administration. However, the long-term antihypertensive effect of GSPE in animals with established HTN has not been investigated. Thus, the aim of this study was to evaluate if GSPE shows a blood pressure-lowering effect in hypertensive rats after its administration for 3 weeks. Wistar rats were fed a standard or CAF diet for 12 weeks, and during the last 3 weeks, animals were administered vehicle, captopril or a low dose of GSPE (25 mg per kg body weight, bw). Both systolic and diastolic blood pressure (SBP and DBP) were monitored weekly. The liver reduced glutathione (GSH) levels, plasma angiotensin converting enzyme activity and endothelial gene expression of eNOS, KLF-2, Sirt-1, NOX4 and ET-1 were studied at the end-point. The results demonstrated that 3 weeks of CAF diet administration with 25 mg per kg bw GSPE significantly reduced SBP and DBP in hypertensive rats. GSPE induced the upregulation of Sirt-1 gene expression and downregulated the vasoconstrictor ET-1, suggesting the vasoprotective effect of GSPE and increased the antioxidant GSH activity. The administration of 25 mg per kg bw GSPE for 3 weeks significantly reduced BP in CAF diet fed animals with established HTN.